Realization of New Mutually Coupled Circuit Using CC-CBTAs - Koksal, M.; Ayten, U. E.; Sagbas, M. (SPRINGER BIRKHAUSER, 2012)
A novel circuit for the realization of the mutually coupled circuit using three current-controlled current backward transconductance amplifiers (CC-CBTAs) as active components is proposed. The active mutually coupled circuit structures are also called the synthetic transformers. The circuit is derived by using three floating simulated inductors that are connected as the T-type transformer model. The circuit has the following attractive advantages: (i) The values of a primary self-inductance, a secondary self-inductance and a mutual inductance can be independently tuned by the transconductance gain of the CC-CBTAs; (ii) The circuit uses three grounded capacitors that are suitable from the point of integrated circuit implementation; (iii) It uses only three active components; (iv) It has a good sensitivity performance with respect to the tracking errors; (v) Both positive and negative couplings are achieved and the coupling coefficient is not limited by 1 in magnitude; (vi) Symmetrical coupling is achieved without necessitating any matching condition; (vii) The proposed circuit has a floating structure.
Keywords: Mutually coupled circuits; Synthetic transformer; Current backward transconductance amplifier; Active circuits; Bandpass filter; Electronic tunability; FLOATING INDUCTANCE; SIMULATOR; TRANSFORMER; CAPACITANCE; FILTERS; Engineering